2020
DOI: 10.1038/s41598-020-66981-z
|View full text |Cite
|
Sign up to set email alerts
|

IgM antibodies against malondialdehyde and phosphorylcholine in different systemic rheumatic diseases

Abstract: the pReciSeSADS clinical consortium*, Marta Alarcon-Riquelme 1,3 & Johan frostegård 1 ✉ igM antibodies against phosphorylcholine (anti-pc) and malondialdehyde (anti-MDA) may have protective properties in cardiovascular and rheumatic diseases. We here compare these antibodies in systemic rheumatic conditions and study their properties. Anti-pc and anti-MDA was measured using ELISA in patients with SLE (374), RA (354), Mixed connective tissue disease (MCTD, 77), Systemic sclerosis (SSc, 331), Sjögren's syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
(88 reference statements)
1
7
0
Order By: Relevance
“…Also in SLE, we reported that anti-PC is associated with protection and in relation to prevalence of atherosclerotic plaques and other disease manifestations [55][56][57][58]83], which has been confirmed by other researchers [59,60]. Among subclasses and isotypes, the protective properties of anti-PC are mainly present in IgM and IgG1 [57,61,142].…”
Section: Factors In Common In Atherosclerosis Cvd and Sle: Inflammati...supporting
confidence: 77%
See 2 more Smart Citations
“…Also in SLE, we reported that anti-PC is associated with protection and in relation to prevalence of atherosclerotic plaques and other disease manifestations [55][56][57][58]83], which has been confirmed by other researchers [59,60]. Among subclasses and isotypes, the protective properties of anti-PC are mainly present in IgM and IgG1 [57,61,142].…”
Section: Factors In Common In Atherosclerosis Cvd and Sle: Inflammati...supporting
confidence: 77%
“…Traditional risk factors Age [25,27,45] Dyslipidemia (including different abberations in lipids) [25,39,49] Hypertension [25] Diabetes [25] Smoking [25] Nontraditional risk factors Antiphospholipid antibodies [25,[50][51][52][53][54] Other SLE manifestations (especially renal) [1,2,25,[27][28][29][30][31][32][33][34][35][36][37]45] Cortisone treatment [25,27,39,45] Low levels of natural antibodies including antiphosphorylcholine [55][56][57][58][59][60][61] Note: Commonly, in CVD in the general population, the risk factor concept is related to causation; for example, a risk marker is determined to be a risk factor when treatment of the risk marker decreases CVD (as defined by myocardial infarction (MI), stroke, peripheral artery disease, and angina). Since SLE is a rare disease, such treatment studies have not often been done, so risk markers with substantial human data are also included in the concept.…”
Section: Table 1 Independent Risk Factors For Cardiovascular Disease ...mentioning
confidence: 99%
See 1 more Smart Citation
“…IgM anti-PC promote polarization of T regulatory cells, from atherosclerotic plaques, another immunomodulatory and anti-inflammatory property of anti-PC with direct relevance for the present study 33 . Moreover, IgG1, more than IgG2, anti-PC has protective properties associated with less atherosclerosis progress, less vulnerable plaques and mortality in CKD 29 , 30 , 34 and IgA anti-PC is associated with favorable atherosclerosis progress 29 . It is likely that IgA anti-PC also shares at least some of these protective properties with other anti-PC subclasses and isotypes but more studies on IgA anti-PC are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the context of rheumatic disease, an inverse correlation between anti-PC antibodies and, organ damage and disease activity in SLE patients has been demonstrated (95,96). Although the exact mechanism(s) underlying the protective effects of anti-PC antibodies is still under investigation, anti-inflammatory and cardioprotective benefits of anti-PC antibodies in SLE and also Sjögren's syndrome and mixed connective tissue disease are associated with regulatory T cell polarisation, oxidised low density lipoprotein uptake inhibition and enhanced apoptotic cell clearance (96)(97)(98)(99). Interestingly, IgM anti-PC antibodies are greatly increased in response to ES-62 in murine models of lupus and in high calorie diet (HCD)-fed mice (82,89).…”
Section: Serendipitous Induction Of Anti-inflammatory Antibodiesmentioning
confidence: 99%